Applying Translational Research in University-Industry Collaboration through Crab Farming for Socio-Economic Alleviation of Disadvantage Communities - Rugayah, Hashim; Saiful Bahari, Mohd Yusoff; Zaidi, Mohd Aminuddin; Aida Maria, Ismail (AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK, 2020)
Innovations can be translated into social entrepreneurship to benefit disadvantage communities. This paper narrates the social entrepreneurship project between Universiti Malaysia Sarawak (UNIMAS) and Universiti Teknologi MARA Cawangan Selangor (UCS). UNIMAS’s crab cage innovation was implemented at the Pulau Salak community in Santubong, Sarawak. The social entrepreneurship expertise was provided by UCS. The translational research cum collaborative project has improved the living standards by exploiting on the built environment which is perfect for crab farming. Aquaculture as a cash crop will ensure food security and significant economic growth. Translational research projects should be the new normal afterthe pandemic lockdowns.